2007
DOI: 10.1111/j.1468-3156.2007.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of running an anxiety management group for people with a learning disability using a cognitive behavioural intervention

Abstract: Accessible summary• We ran a group for 6 people with a learning disability who worry a lot. The group last for 12 weeks and each person in the group brought someone with them. • People said they found the group helpful. People said they learnt ways to cope when they get worried. • This research will help staff to think about how they can help people who worry a lot. More research is needed to find out which bits of the group were most helpful. SummaryAn anxiety management group utilizing a cognitive behavioura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 15 publications
3
34
0
Order By: Relevance
“…Three of the five participants involved in the Transformers programme exhibited fewer incidents of challenging behaviour following treatment. These results are consistent with recent research which shows that CBT interventions can improve coping strategies and reduce challenging behaviour in people with an ID (Douglass et al, 2007;Lindsay et al, 2004;Willner et al, 2005;Willner et al, 2013).…”
Section: Discussionsupporting
confidence: 95%
“…Three of the five participants involved in the Transformers programme exhibited fewer incidents of challenging behaviour following treatment. These results are consistent with recent research which shows that CBT interventions can improve coping strategies and reduce challenging behaviour in people with an ID (Douglass et al, 2007;Lindsay et al, 2004;Willner et al, 2005;Willner et al, 2013).…”
Section: Discussionsupporting
confidence: 95%
“…The results suggest that some participants were more likely to talk about their problems and receive support from others by the end of the group. This is similar to finding by Douglass et al (2007) where at the end of their group, two participants reported they had developed more confidence to approach staff when they were worried. ' The two major causes of anxiety identified by participants were other people and change.…”
Section: Discussionsupporting
confidence: 87%
“…This is significantly smaller than LIFT groups, typically with 20-30 people. Research into therapeutic groups for people with intellectual disabilities report sizes between six and nine (Douglass et al, 2007;Rose, 2010). Although this increased demand in resources is something the local teams agreed to commit to for the pilot, it is unclear whether this is cost effective and sustainable within the context of a resource-pressured NHS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Implementing cognitive challenging for adults with ID remains a clinical challenge (Douglass, Palmer, & O'Connor, 2007) and requires a more comprehensive level of description in the literature (Dagnan & Jahoda, 2006). To progress the use of cognitive challenging for people with ID in both research and practice, this article introduces a framework to modify cognitive challenging and also present results from a pilot evaluation of a broader CBT-ID group programme for anxiety.…”
Section: Introductionmentioning
confidence: 99%